Atomic structures of twin boundaries in hexagonal close-packed metallic crystals with particular focus on Mg - Zongrui Pei (Nature Portfolio, 2017)
Structural materials: at the boundary between twins A group of atomic defects that are critical to the mechanical properties of common metals is investigated by researchers in Germany and the Czech Republic. Zongrui Pei from the Max-Planck-Institut für Eisenforschung and co-workers identify the types of structural aberration that can exist in materials such as magnesium, zirconium and titanium. A twin boundary occurs where the regular atomic structure in one region becomes misaligned from that in the next. For one specific atomic arrangement, known as a hexagonal close-packed structure, the atomic structures of such defects are not very well understood. Pei et al. use ab-initio methods and large-scale atomistic simulations to show that two types of twin boundaries can occur in magnesium: glide twin boundaries and reflection twin boundaries. They show that mechanical instability makes the former difficult to see experimentally.